Evaluation of Domestic Violence Screening and Positive Screen Rates in Rural Hospital Emergency Departments - Devin K Trinkley; Sandra H. Bryan; Karen Gabel Speroni; Ruth Ann Jones; Hubert A. Allen (Rural Nurse Organization; Binghamton University, 2012)
Introduction: Although Emergency Department (ED) patients are to be screened for domestic violence (DV), not all patients are screened. The objectives of this study were to quantify rural community hospital overall ED patient DV screening rates and positive DV screen rates. Methods: In this retrospective chart review, a total of 1,200 of 13,336 patient ED visits were randomly selected. Patients were excluded who presented with cardiac or respiratory arrest, mental health diagnoses, or major trauma; were transferred or arrived from long term care facilities; or were victims of sexual assault. Data was collected on demographics, language, and three key factors for DV per nurse documentation (reported physical or sexual assault, fear, and objective signs). This study was reviewed by an Institutional Review Board. Results: Eighty-eight percent (N=1,056) of rural ED patients in this study sample had documentation for DV screening being completed. Of these, 2% (n=21) had documentation positive for DV. Of those positive, the majority were female (62%), English speaking (86%) patients with an average age of 29 years. Eighty-six percent reported assault, 33% reported fear, and 19% had objective signs of DV. Conclusions: The overall DV screening rate of 88% supports the recommendation that all hospitals should ensure they have 100% DV screening rate compliance. The low 2% positive DV screening rate suggests the need for future research to determine DV screening barriers for both nurses and patients.   Keywords: Domestic Violence; Screening; Rural Hospitals; Emergency Departments